2005
DOI: 10.1242/jcs.01651
|View full text |Cite
|
Sign up to set email alerts
|

Repeated exposure of human skin fibroblasts to UVB at subcytotoxic level triggers premature senescence through the TGF-β1 signaling pathway

Abstract: Premature senescence of human diploid fibroblasts (HDFs) can be induced by exposures to a variety of oxidative stress and DNA damaging agents. In this study we developed a robust model of UVB-induced premature senescence of skin HDFs. After a series of 10 subcytotoxic (nonproapoptotic) exposures to UVB at 250 mJ/cm 2 , the socalled biomarkers of senescence were markedly expressed: growth arrest, senescence-associated β-galactosidase activity, senescence-associated gene overexpression, deletion in mitochondrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
186
2
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 233 publications
(207 citation statements)
references
References 64 publications
(88 reference statements)
16
186
2
3
Order By: Relevance
“…In addition, it has been shown that oxidative stress and stress-induced TGF-β1 overexpression can induce premature senescence that can be blocked by antioxidants or antibodies against TGF-β1 or its respective receptor (32,35,48). However, in our experiments the presence of antioxidants or an inhibitor of TGF-β receptor, during the whole period of irradiation and the time needed for the appearance of the senescent phenotype, was unable to prevent this phenomenon.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…In addition, it has been shown that oxidative stress and stress-induced TGF-β1 overexpression can induce premature senescence that can be blocked by antioxidants or antibodies against TGF-β1 or its respective receptor (32,35,48). However, in our experiments the presence of antioxidants or an inhibitor of TGF-β receptor, during the whole period of irradiation and the time needed for the appearance of the senescent phenotype, was unable to prevent this phenomenon.…”
Section: Discussioncontrasting
confidence: 70%
“…Next, we tried to investigate the mechanisms responsible for the induction of premature senescence by repeated doses of ionizing radiation. It has been shown that ionizing radiation generates reactive oxygen species and activates TGF-β, two well known inducers of premature senescence (31,32). In addition, it also provokes the activation of p38 MAPK ( Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The value of the technology of low density DNA arrays used in this study has been extensively demonstrated previously in a variety of models, as diverse as hepato-toxicology (de Longueville et al 2002), breast cancer (Gillet et al 2006), skin irritation (Borlon et al 2007b), response to UVB stress (Borlon et al 2007c;Debacq-Chainiaux et al 2005) and cell senescence (de Magalhaes et al 2004;Pascal et al 2005;Zdanov et al 2006). Numerous verifications with real time RT-PCR have been done on all these models.…”
Section: Introductionmentioning
confidence: 79%
“…More than 40 verifications with real-time RT PCR of the relative gene expression level obtained with this microarray have already been done in several senescence-related models (Borlon et al 2007a;de Magalhaes et al 2004;Debacq-Chainiaux et al 2005;Zdanov et al 2006). Nevertheless, further verifications were done in the studies.…”
Section: Validation Of Relative Gene Expression By Real Time Rt-pcrmentioning
confidence: 99%
See 1 more Smart Citation